2019
DOI: 10.3390/insects10020041
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and Environmental Factors Influencing Stage Persistence and Abundance of the Bamboo Mosquito, Tripteroides bambusa (Diptera: Culicidae), across an Altitudinal Gradient

Abstract: The bamboo mosquito, Tripteroides bambusa (Yamada) (Diptera: Culicidae), is a common insect across East Asia. Several studies have looked at the ecology of Tr. bambusa developmental stages separately, but little is known about the factors associated with the persistence (how often) and abundance (how many individuals) of Tr. bambusa stages simultaneously studied across a heterogeneous landscape. Here, we ask what environmental and landscape factors are associated with the persistence and abundance of Tr. bambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Secondly, Hainan Island is experiencing rapid development, urbanization, road construction and other developments, which may have caused environmental modifications that in turn affect larval habitability and mosquito survival of some species. Many studies have demonstrated that changes in the landscape can affect the distribution of the local mosquito vectors [ 55 57 ]. Future sampling should cover more diverse ecological settings, so that results can reflect the true species diversity of the mosquito community.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Hainan Island is experiencing rapid development, urbanization, road construction and other developments, which may have caused environmental modifications that in turn affect larval habitability and mosquito survival of some species. Many studies have demonstrated that changes in the landscape can affect the distribution of the local mosquito vectors [ 55 57 ]. Future sampling should cover more diverse ecological settings, so that results can reflect the true species diversity of the mosquito community.…”
Section: Discussionmentioning
confidence: 99%
“…We also downloaded images for the Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI), both of which are considered proxies for vegetation growth ( Pettorelli et al., 2005 ) and have been extensively used to study the ecology of mosquitoes ( Hurtado et al., 2018b ; Chaves et al., 2019 ; Poh et al., 2019 ; Rigg et al., 2019 ; Nguyen et al., 2020 ; Chaves & Friberg, 2021 ) and other insect vectors ( Kitron et al., 1996 ). The images for vegetation indices were downloaded for the multiple spatial scales encompassed by MODIS, Landsat 8 and Sentinel 2.…”
Section: Methodsmentioning
confidence: 99%
“…When fitting the models, all selected covariates were demeaned to ease their interpretation in terms of changes above or below their means ( Chaves et al., 2018 ). We selected the best models through the minimization of the Akaike Information Criterion (AIC), a metric that trades-off model goodness-of-fit and parameter number, employing a strategy of backward elimination, where models are simplified by comparing “nested” models with the same number of parameters that are not significantly different from the “parent” model that considered all variables that are left out in each of the simplified “nested” models ( Chaves, 2016 ; Chaves & Moji, 2018 ), or until there were no significant differences through a Chi-square likelihood ratio test between the model minimizing AIC and simplified versions of such model ( Chaves et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the abundance of temporally frequent high (30 m for Landsat 8) and medium (250 m for Moderate Resolution Image Spectroradiometer, MODIS) resolution satellite images at Mt. Konpira ( Chaves et al., 2019 ), allow to estimate time series of vegetation growth indices, such as the Normalized Difference Vegetation Index (NDVI) and the Enhanced Vegetation Index (EVI), which have been related with spatial patterns of insect vector abundance ( Kitron et al., 1996 ) and mosquito population dynamics ( Hurtado et al., 2018 ; Poh et al., 2019 ; Rigg et al., 2019 ). Thus, Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the altitudinal gradient of Mt. Konpira, one of the highest mountains in Nagasaki City ( Hoshi et al., 2017 ), generates environmental and landscape gradients that allows the identification of environmental and landscape conditions favoring the presence and abundance of mosquito species ( Chaves et al., 2019 , 2015 ; Chaves and Moji, 2018 ). Here, we present results from a two-yearlong study where we recorded Ae.…”
Section: Introductionmentioning
confidence: 99%